2018
DOI: 10.9755/ejfa.2018.v30.i4.1665
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of lactation and machine milking in dromedary she-camel

Abstract: Dromedary camels have the capability and the genetic potential to achieve high levels of milk production. However, systematic breeding programs to increase milk production are not common in this species. Dromedary camels are not well adapted to machine milking. Milk removal obviously requires in most farms a pre-stimulation through calf suckling before the milking machine can completely harvest the stored milk. In camels, most of the milk is stored in the alveolar compartment (>90-95%) of the udder. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…According to literary sources [28], [29], [30], [31], [32], the increase in the service period causes an increase in the total amount of milk during lactation. It causes a deterioration in the reproductive capacity of cows.…”
Section: Resultsmentioning
confidence: 99%
“…According to literary sources [28], [29], [30], [31], [32], the increase in the service period causes an increase in the total amount of milk during lactation. It causes a deterioration in the reproductive capacity of cows.…”
Section: Resultsmentioning
confidence: 99%
“…New research emphasized that the frequency of bimodalities with both pre-stimulation and without pre-stimulation was higher at high vacuum level than at low vacuum level [19]. The use of high milking vacuum for camels could lead to udder health problems reflected by a high somatic cell count in the produced milk and a negative impact on the health status of the teats [18]. A positive relationship between increasing working vacuum and somatic cell counts in the milk has been found in buffalo [38] and other dairy species [14,[39][40][41].…”
Section: Influence Of the Vacuum Level In The Milking Machine On Milk...mentioning
confidence: 99%
“…Moreover, it should be noted that insufficient pre-stimulation can lead to poor milking performance, especially in cows, camels, and buffalo, which have small udder cisterns and large amount of alveolar milk [1,[16][17][18][19]. A new study has shown that efficient machine milking requires an optimal interaction between the alveolar milk ejection in the udder induced by hormonal posterior hypophyseal oxytocin release, smooth muscle contraction of the alveolar myoepithelial cells and thereafter the milk removal by the milking machine [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar milk, however, is only available if it is actively expelled as a result of the concentration of oxytocin in the blood during milking [11]. Also, both are very sensitive to environmental stimulus before and during milking which explains the disrupted milk ejections observed for buffaloes [8,12] and camels [13,14]. In addition, because of external udder morphology similarities with bovine species, these animals are usually milked with the same milking equipment but with different settings to respect the physiological needs of each species [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, both are very sensitive to environmental stimulus before and during milking which explains the disrupted milk ejections observed for buffaloes [8,12] and camels [13,14]. In addition, because of external udder morphology similarities with bovine species, these animals are usually milked with the same milking equipment but with different settings to respect the physiological needs of each species [14][15][16]. Evaluation of milkability characteristics in nonbovine dairy animals has been reported to improve milking efficiency, reduce working vacuum on-time on empty teats [2,17,18] and could be used to select suitable animals with similar milkability traits for an optimal milking process [2,19].…”
Section: Introductionmentioning
confidence: 99%